Hybrid Quadrupole-Orbitrap Mass Spectrometry for Quantitative Measurement of Quorum Sensing Inhibition - Todd, Daniel A. (J Microbiol Methods, 2016)
Drug resistant bacterial infections cause significant morbidity and mortality worldwide, and new strategies are needed for the treatment of these infections. The anti-virulence approach, which targets non-essential virulence factors in bacteria, has been proposed as one way to combat the problem of antibiotic resistance. Virulence in methicillin-resistant Staphylococcus aureus (MRSA) and many other Gram-positive bacterial pathogens is controlled by the quorum sensing system. Thus, there is excellent therapeutic potential for compounds that target this system. With this project, we have developed and validated a novel approach for measuring quorum sensing inhibition in vitro. Ultraperformance liquid chromatography coupled to mass spectrometry (UPLC-MS) was employed to directly measure one of the important outputs of the quorum sensing system in MRSA, auto-inducing peptide I (AIP I) in bacterial cultures. The method for AIP detection was validated and demonstrated limits of detection and quantification of range of 0.0035 µM and 0.10 µM, respectively. It was shown that the known quorum sensing inhibitor ambuic acid inhibited AIP I production by a clinically relevant strain of MRSA, with an IC(50) value of 2.6 ± 0.2 µM. The new method performed similarly to previously published methods using GFP reporter assays, but has the advantage of being applicable without the need for engineering of a reporter strain. Additionally, the mass spectrometry-based method could be applicable in situations where interference by the inhibitor prevents the application of fluorescence-based methods.